Outcomes analysis of hospital management model in restricted budget conditions. Issue 2 (3rd March 2016) - Vaseva, Virsavia; Voynov, Latchezar; Donchev, Toni; Popov, Rumen; Mutafchiyski, Ventsislav; Aleksiev, Lyubomir; Kostadinov, Krassimir; Petrov, Nikolay
ABSTRACT: Facing conditions of market economy and financial crisis, the head of any healthcare facility has to take adequate decisions about the cost-effective functioning of the hospital. Along with cost reduction, the main problem is how to maintain a high level of health services. The aim of our study was to analyse the quality of healthcare services after the implementation of control over expenses due to a reduction in the budgetary resources in Military Medical Academy (MMA, Sofia, Bulgaria). Data from the hospital information system and the Financial Department about the incomes and expenditures for patient treatment were used. We conducted a retrospective study on the main components of clinical indicators in 2013 to reveal the main problems in the hospital management. In 2014, control was imposed on the use of the most expensive medicines and consumables. Comparative analysis was made of the results of the medical services in MMA for 2013 and 2014. Our results showed that despite the limited budget in MMA over the last year, the policy of control over operational costs succeeded in maintaining the quality of healthcare services. While reducing the expenses for medicines, consumables and laboratory investigations by ∼26%, some quality criteria for healthcare services were observed to be improved by ∼9%. Financial crisis and budget reduction urge healthcare economists to create adequate economical instruments to assist the normal functioning of hospital facilities. Our analysis showed that when a right policy is chosen, better results may be achieved with fewer resources.